National culture moderators of pay for individual performance and the financial performance of multinational enterprises - Posthuma, Richard A.; Campion, Emily D.; Campion, Michael A.; Zhang, Haiyan (Applied psychology, 2023)
We examined the effectiveness of pay for individual performance (PFIP) in companies operating in multiple cultures. With the use of data from 308 multinational enterprises (MNEs) collected by IBM's WorkTrends™ project, we tested hypotheses regarding the moderating influence of the nine dimensions of the GLOBE country culture model on the relationship between PFIP and changes in financial performance over time. Multiple employees per firm (mean N = 24.7 employees) reported the extent there was a PFIP climate (PFIPc) in their firm. We matched these data at the firm level to changes in net income per employee over 4 years from the Wharton Research Data Service (WRDS). Consistent with predictions developed from contingency and cross‐cultural theories, after including relevant controls, we found the positive relationship between PFIPc and subsequent MNE performance is greater in cultures higher in future orientation, institutional collectivism and uncertainty avoidance and also lower in in‐group collectivism, power distance and humane orientation.